2017
DOI: 10.1073/pnas.1708247114
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis controls NET generation and mediates complement activation, endothelial damage, and autoimmune vasculitis

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) constitutes life-threatening autoimmune diseases affecting every organ, including the kidneys, where they cause necrotizing crescentic glomerulonephritis. ANCA activates neutrophils and activated neutrophils damage the endothelium, leading to vascular inflammation and necrosis. Better understanding of neutrophil-mediated AAV disease mechanisms may reveal novel treatment strategies. Here we report that ANCA induces neutrophil extracellular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(203 citation statements)
references
References 51 publications
(60 reference statements)
2
193
0
3
Order By: Relevance
“…This may not exclusively be the case for systemic lupus erythematosus (SLE), but also for other autoimmune diseases. One such example that causes AKI may be ANCA-associated vasculitis [19]. fore facilitated the assessment of ferroptosis-interference in vivo in models of AKI.…”
Section: Can Autoimmunity Be Explained By Failure To Remove Necroticmentioning
confidence: 99%
“…This may not exclusively be the case for systemic lupus erythematosus (SLE), but also for other autoimmune diseases. One such example that causes AKI may be ANCA-associated vasculitis [19]. fore facilitated the assessment of ferroptosis-interference in vivo in models of AKI.…”
Section: Can Autoimmunity Be Explained By Failure To Remove Necroticmentioning
confidence: 99%
“…Transplantation of bone marrow harvested from Ripk3 -deficient mice into wild type mice protected the recipients from glomerular injury [18]. This implies a role of RIPK3-mediated necroptosis for neutrophil necroptosis and neutrophil extracellular trap-related glomerular injury, a concept supported by effective in vitro experiments by the same group [18].…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
“…Transplantation of bone marrow harvested from Ripk3 -deficient mice into wild type mice protected the recipients from glomerular injury [18]. This implies a role of RIPK3-mediated necroptosis for neutrophil necroptosis and neutrophil extracellular trap-related glomerular injury, a concept supported by effective in vitro experiments by the same group [18]. Indeed, neutrophil necroptosis has also been reported using other triggers, for example, phorbol 12-myristate 13-acetate or crystalline microparticles using neutrophils isolated from Ripk3- ( and Mlkl)- deficient mice [19, 20].…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] NETs also involve in the development of inflammation through inducing the release of cytokine by airway epithelial cells. Our experimental data suggested that NETs Increasing evidence has shown that NETs and their components cause damage of endothelial and epithelial cells, thus to impair pulmonary function and accelerate the progress of chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%